2016
DOI: 10.1002/2016gl069513
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence of the Hainan mantle plume by receiver function analysis in southern China

Abstract: The Lei‐Qiong region is the largest igneous province in southern China and may be a surface expression of a mantle plume beneath the region (the Hainan mantle plume). To investigate the existence of the Hainan mantle plume, we used P‐to‐S receiver function to image the major seismic discontinuities beneath this region with a regional dense broadband array. We found that the Moho discontinuity beneath the Leizhou Peninsula, mostly covered by Cenozoic basaltic outcrops, is 10–15 km deeper compared to the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 53 publications
6
54
0
Order By: Relevance
“…If we assume that the true depth of the d 410 is 410 km, the apparent depression suggests an overall lower‐than‐normal upper mantle and crustal velocities with magnitude of −1.1% to −1.5% [ Gao and Liu , ], a value that is comparable to results from seismic tomography investigations [e.g., Montelli et al , ; Li et al , , ; Wang and Huang , ; Le et al , ; Xia et al , ]. The maximum MTZ thinning of 21 km is found beneath southern Vietnam, corresponding to a thermal anomaly of about +180 K. The amount of thinning in the Hainan area is about 15 km, which is similar to those reported in previous studies covering this area [ Wang and Huang , ; Huang , ; H. Huang et al , ; Wei and Chen , ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…If we assume that the true depth of the d 410 is 410 km, the apparent depression suggests an overall lower‐than‐normal upper mantle and crustal velocities with magnitude of −1.1% to −1.5% [ Gao and Liu , ], a value that is comparable to results from seismic tomography investigations [e.g., Montelli et al , ; Li et al , , ; Wang and Huang , ; Le et al , ; Xia et al , ]. The maximum MTZ thinning of 21 km is found beneath southern Vietnam, corresponding to a thermal anomaly of about +180 K. The amount of thinning in the Hainan area is about 15 km, which is similar to those reported in previous studies covering this area [ Wang and Huang , ; Huang , ; H. Huang et al , ; Wei and Chen , ].…”
Section: Discussionmentioning
confidence: 53%
“…Previous MTZ studies in Southeast Asia are mostly restricted in the Hainan Island region located in the northeastern part of the study area (Figure ). Most studies [ Wang and Huang , ; H. Huang et al , ; Wei and Chen , ] reveal an MTZ of about 25 km thinner than the normal value of 250 km in the IASP91 and most other earth models, which is attributed to a mantle plume originating from the lower mantle. The MTZ beneath the vast majority of the ICP has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar isotopically enriched N‐MORB rocks are common in oceanic ridge segments with large plume‐ridge distances, and those elemental depleted but isotopically enriched sources are proposed to be decompression remelting of elementally depleted residue of plume materials (Yang et al, ). The existence of off‐axis Hainan Plume has received support from increasing geophysical, petrologic, and geochemical evidence (Lei et al, ; X. C. Wang et al, ; Wang et al, ; S. Wei & Chen, ). Therefore, a possible petrogenesis of ~16 Ma isotopically enriched N‐MORBs of the South China Sea is that the head of Hainan Plume have already arrived beneath the lithosphere since the early Miocene and the ridge suction (Y. G. Xu et al, ) introduced elementally depleted residue of plume materials into the mid‐ocean ridge subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…However, the OIB‐type intraplate volcanism of the South China continental margin paused during the Oligocene but resumed since the earliest Miocene and reached a peak during late Pliocene and early Pleistocene (X. L. Huang et al, ; Y. G. Xu et al, ; P. Yan et al, ; Zhu et al, ). Recent studies identified the Hainan Plume based on seismic imaging (Lebedev & Nolet, ; Lei et al, ; S. Wei & Chen, ), and the existence of this plume is supported by petrologic and geochemical evidence from the late Cenozoic Hainan flood basalts (X. C. Wang et al, ; Wang et al, ). Furthermore, the late Cenozoic OIB‐type intraplate volcanism in the South China Sea and the Indochina region (Figure a) are thought to be the products of the Hainan Plume (Wang et al, ; Q. Yan et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Hainan Island is separated from the South China Block by the Qiongzhou Strait (Figure ). Global and regional tomographic results (Huang, ; Lebedev & Nolet, ) indicate that a clear low seismic wavespeed anomaly occurs beneath Hainan Island and likely extends to the lower mantle with an estimated radius of 40–80 km (Lei et al, ; Wei & Chen, ). Geochemical studies have shown that large quantities of extensive basaltic lava are observed in Hainan Island, which show the compositions of OIB and Dupal‐like enriched mantle type 2 isotopic signatures (Ho et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%